Urine Chemical Profile of Boerka Crossbreed Goats of Indonesia at Sanda Village, Tabanan, Bali - Freitas, Merlinde da Costa; Batan, I Wayan; Pemayun, I Gusti Agung Gde Putra (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Boerka Goat is a small ruminant that has the potential to be developed to meet the demand for goat meat products. One of the methods to examine livestock health is through urinalysis. Qualitative urinalysis testing includes an examination of leukocytes, protein, bilirubin, urobilinogen, ketones, nitrites, pH, specific gravity, red blood cells, and glucose. This research aims to identify the chemical profile of boer-kacang goat urine chemical profile. During analysis a total of 16 urine sample of boer-kacang crossbreed goats from Walung Amertha Farm, Sanda Village, Pupuan, Tabanan were analyzed.  The urine samples taken were midstream urine. Sampling was carried out once then continue with the dipstick testing about three times on each sample.  The analysis data were tabulated and averaged before be presenting in a tabular form with descriptive analysis.  The results of the study on the chemical profile of boerka goat urine showed leukocytes positive1+ in 19% goats, bilirubin 1+ in 13% goats, nitrite positive in 6% goats, positive red blood cells in 13% goats, while the specific gravity with an average of 1.002 and the average value of pH with 8.25.  Based on the research, it concludes that the urine chemical profile of boer-kacang goat positively contains erythrocytes, leukocytes, bilirubin, and nitrite although other profiles such as protein, urobilinogen, ketones, and glucose is undetected.  Urine specific gravity measured using a dipstick was 1,000-1,010 whereas the acidity level/pH is normal.